Assessment of Muscle Activity and Co-contraction in Knee and Ankle Joints during Forward and Backward Walking in Healthy Individuals - Neda Asri; Nader Farahpour; Leila Ghazaleh (مجله پژوهش در علوم توانبخشی, 2018)
Introduction: Backward walking trainings are recommended to improve lower limb muscle performance in patients with joint injuries. The purpose of this study was to investigate muscles activity and co-contraction in ankle and knee joints during forward walking (FW) and backward walking (BW) in healthy individuals.